Preparation method of lithium iron phosphate precursor adaptive to high capacity and high compaction

By employing a two-step precipitation reaction and the use of surfactants, a compound-structured lithium iron phosphate was prepared, which solved the problems of insufficient tap density and electrochemical stability in the existing technology, and realized high-capacity and high-tap lithium iron phosphate materials.

CN120922838APending Publication Date: 2025-11-11HUBEI THREE GORGES LAB +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511077693.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing iron phosphate preparation processes struggle to balance high tap density and high ion diffusion rate, and compounding processes suffer from uneven component distribution and weak interfacial bonding, resulting in insufficient electrochemical stability of the materials.

Method used

By employing a two-step precipitation reaction and adding surfactants, cubic phase iron phosphate was synthesized via a one-step hydrothermal synthesis and a two-step co-current synthesis of porous iron phosphate, thus preparing a composite structure of iron phosphate, which improved crystallinity and interfacial bonding.

Benefits of technology

The prepared compound structure of lithium iron phosphate exhibits high tap density and superior electrochemical stability, with a tap density exceeding 2.5 g/cm3 and a 1C discharge capacity of over 145 mAh/g, thus improving the performance of lithium iron phosphate materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing a ferrous solution and a phosphorus salt solution in proportion, then dropwise adding hydrogen peroxide into the mixed solution, adding a proper amount of polyaspartic acid and / or oligomeric ethoxylated fatty acid methyl ester, and firstly obtaining a part of iron phosphate slurry by a hydrothermal synthesis method; taking the iron phosphate slurry as a reaction base solution, then dropwise adding an acidified ferric salt solution and a phosphorus salt mixed solution in a parallel flow manner to synthesize iron phosphate, and aging to obtain an iron phosphate precursor precipitate; filtering, washing, drying and crushing the iron phosphate precursor precipitate to obtain iron phosphate dihydrate powder; and sintering and sieving the iron phosphate dihydrate powder to obtain the anhydrous iron phosphate. According to the invention, iron phosphate with a compound structure is obtained through two-step synthesis, and lithium iron phosphate prepared from the material has the characteristics of relatively high compaction density and large capacity, and has certain practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the preparation technology of lithium-ion battery cathode material precursors, specifically to a graded iron phosphate and its preparation method. Background Technology

[0002] Lithium iron phosphate (LiFePO4) batteries have been widely used in electric vehicles, energy storage devices, and other fields in recent years. As a precursor to lithium iron phosphate (LiFePO4), the cathode material of lithium-ion batteries, iron phosphate (FePO4) directly affects the energy density, cycle life, and rate performance of the final cathode material due to its structure, morphology, and electrochemical performance. Traditional iron phosphate preparation processes often employ solid-state or liquid-state methods, such as high-temperature solid-state sintering, hydrothermal synthesis, or co-precipitation. However, iron phosphate materials prepared by a single method often suffer from drawbacks such as a lack of uniform morphology and structure. For example, solid-state methods easily lead to particle agglomeration and inhomogeneous crystal structures, while liquid-state methods, although producing materials with uniform particle size, exhibit poor conductivity, making it difficult to simultaneously meet the dual requirements of high tap density and high ion diffusion rate.

[0003] In recent years, researchers have attempted to improve the performance of iron phosphate through doping modification, carbon coating, or nanostructuring, but existing technologies still have significant shortcomings. For example, CN107732201A indicates that although carbon coating can improve conductivity, excessive carbon layers will reduce the tap density of the material; CN202110204239A indicates that single-structure iron phosphate materials are prone to particle breakage due to anisotropic expansion during charge and discharge, which in turn affects battery life.

[0004] To address the aforementioned issues, structural compounding technology has gradually become a research hotspot. Its core lies in optimizing the overall material performance through synergistic effects by combining iron phosphate components with different morphologies (such as micron-sized bulk particles and nano-sized particles) or different crystal forms (such as amorphous and crystalline phases). However, existing compounding processes mostly employ mechanical mixing or stepwise synthesis, resulting in uneven component distribution and weak interfacial bonding, leading to insufficient electrochemical stability of the materials. Furthermore, the controllability of compounded structures and methods for large-scale preparation still lack systematic research, making it difficult to achieve a balance between performance and cost. Summary of the Invention

[0005] To address the above problems, the present invention aims to provide a method for preparing a composite structure of lithium iron phosphate. This method involves a two-step precipitation reaction and the addition of a surfactant to prepare lithium iron phosphate with a complex crystalline structure, which can effectively produce high-capacity and high-compact lithium iron phosphate cathode materials. To achieve the above-mentioned objectives of this invention, the following technical solution is adopted: A method for preparing high-pressure compaction and high-capacity iron phosphate includes the following steps: Step 1: Mix the phosphate solution with the ferrous solution, then add a certain amount of hydrogen peroxide dropwise. After the addition is complete, add polyaspartic acid and / or oligo-ethoxylated fatty acid methyl ester. After keeping warm for a period of time, ferric phosphate slurry is obtained. Step 2: Acidify the ferrous solution by adding phosphoric acid solution dropwise to obtain ferric salt mixed solution A; add ferric salt mixed solution A and phosphate salt mixed solution A dropwise to the ferric phosphate slurry obtained in Step 1, and carry out the synthesis reaction under high speed stirring. Then, after aging, a precipitate is obtained. The precipitate is filtered and washed to obtain a filter cake. The reaction temperature is 40~50℃, the aging temperature is 85~95℃, and the aging time is 1~3h. Step 3: Dry the filter cake, sieve it, and sinter it to obtain anhydrous ferric phosphate.

[0006] In step 1, the ferrous solution includes at least one of ferrous sulfate, ferrous chloride, and ferrous oxalate.

[0007] In step 1, the phosphate salt solution includes at least one solution of ammonium monohydrogen phosphate and ammonium dihydrogen phosphate; the concentration of the phosphate salt solution is 0.5~1 mol / L. In step 1, hydrogen peroxide is pumped into the reactor using a peristaltic pump, and the reaction is carried out under stirring conditions. The pumping rate of the peristaltic pump is 0.5~10 mL / min.

[0008] In step 1, the amount of polyaspartic acid and / or oligo-ethoxylated fatty acid methyl ester added is 1-5 wt‰, which is 1-5 wt‰ of the total mass of phosphate salt and ferrous raw materials.

[0009] The degree of polymerization (n) of the oligoethyl ethoxylated fatty acid methyl esters is typically between 5 and 8.

[0010] In step 2, the hydrothermal reaction temperature is 160-220℃, and the hydrothermal reaction time is 3-8h.

[0011] In step 2, the ferrous solution is acidified with phosphoric acid to a pH of 1.5–2.5 to obtain a mixed ferric salt solution A with a concentration of 0.5–2 mol / L. The phosphate salt solution is then mixed with hydrogen peroxide to obtain a mixed phosphate salt solution A with a pH of 4.0–4.5.

[0012] In step 2, a peristaltic pump is used to add iron salt mixed solution A and phosphate salt mixed solution A dropwise into the iron phosphate slurry, and the reaction is carried out under stirring conditions.

[0013] Preferably, the peristaltic pump has a pumping speed of 25~200 mL / min. The stirring rate of the reaction is 350~500 rpm.

[0014] The washing process includes washing the solid obtained after solid-liquid separation with water until the conductivity is <3500 μS / cm. Preferably, the solid content in the slurry is 10wt%~15wt%. In step 2, the aging reaction temperature is 85~95℃ and the reaction time is 1~3h.

[0015] Further, in step 3, the washing includes: washing the solid obtained after solid-liquid separation with water until the conductivity is <300μS / cm.

[0016] In step 3, the sintering temperature is 400~700℃, and the sintering time is 1~6h. In a preferred embodiment, the calcination temperature is 500~600℃, and the calcination time is 4~6h.

[0017] Another technical solution of the present invention is to provide a high-capacity and high-compact iron phosphate, which is prepared by the method described above.

[0018] The present invention also provides a lithium iron phosphate, which is prepared by using the iron phosphate obtained by the method as raw material, adding lithium carbonate, carbon source and additives, mixing, grinding and sintering.

[0019] The preparation method of the iron phosphate is as follows: cubic phase iron phosphate slurry is obtained by adding surfactant and one-step hydrothermal synthesis, and then two-step co-current synthesis is carried out to obtain monoclinic crystalline iron phosphate, and finally iron phosphate with a complex structure is obtained.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. In the preparation of ferric phosphate, a two-step synthesis is carried out, and different process methods are used to combine the morphology and structure of ferric phosphate at the synthesis stage. The cubic phase ferric phosphate synthesized by the one-step hydrothermal synthesis has the characteristics of high crystallinity and high tap density, while the ferric phosphate synthesized by the two-step co-current synthesis exhibits a porous structure. Through the combination of morphology and structure in the synthesis stage, the distribution of ferric phosphate components is more uniform, the interfacial bonding force is enhanced, and the electrochemical stability is better.

[0021] 2. The compound-structured iron phosphate prepared by this invention has a high tap density. Lithium iron phosphate materials prepared using this material exhibit excellent performance, with a tap density exceeding 2.5 g / cm³. 3 The above indicates a 1C discharge capacity of 145 mAh / g or higher. Detailed Implementation

[0022] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0023] To better understand the present invention, the following embodiments are provided to further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.

[0024] Example 1 (1) Dissolve 417.03g FeSO4·7H2O in 1.5L of deionized water and stir until completely dissolved to obtain ferrous solution. Then add it to a hydrothermal reactor, followed by 464.6g monoammonium phosphate solution. Then slowly add 84.2 mL of 30% H2O2 at a pump rate of 2.5ml / min. After the addition is complete, add 5‰ polyaspartic acid (PASP) and stir to mix evenly. Then raise the temperature to 180℃ and react at a constant temperature for 6 hours. Then cool naturally to room temperature.

[0025] (2) Weigh 1917.03g of ferrous solution and add 5mL of phosphoric acid to acidify to pH 1.5-2.5 to obtain ferric salt mixed solution A. Then weigh 464.6g of monoammonium phosphate solution and add 84.2ml of 30% hydrogen peroxide to obtain phosphate mixed solution. Use the reaction slurry in (1) as the reaction base liquid, and then add the ferric salt mixed solution and phosphate mixed solution dropwise to the reaction vessel at pump rates of 40ml / min and 25ml / min respectively. The synthesis reaction is carried out under the conditions of reaction temperature of 40~50℃ and stirring speed of 400rpm. Then, the mixture is kept at 90~95℃ for 60~80min to obtain precipitate. (3) The precipitate is filtered and then washed with deionized water to obtain a filter cake; after drying, ferric phosphate dihydrate powder is obtained, and then calcined at a temperature of 550℃ for 2-6 hours to obtain anhydrous ferric phosphate.

[0026] Example 2 (1) Dissolve 417.03g FeSO4·7H2O in 1.5L of deionized water and stir until completely dissolved to obtain ferrous solution. Then add it to a hydrothermal reactor, followed by 464.6g monoammonium phosphate solution. Then slowly add 84.2 mL of 30% H2O2 at a pump rate of 2.5ml / min. After the addition is complete, add 5‰ oligoethylene oxyformyl fatty acid methyl ester (OMEE) and stir to mix evenly. Then raise the temperature to 180℃ and react at a constant temperature for 6 hours. Then cool naturally to room temperature.

[0027] (2) Weigh 1917.03g of ferrous solution and add 5mL of phosphoric acid to acidify to pH 1.5-2.5 to obtain ferric salt mixed solution A. Then weigh 464.6g of monoammonium phosphate solution and add 84.2ml of 30% hydrogen peroxide to obtain phosphate mixed solution. Use the reaction slurry in (1) as the reaction base liquid, and then add the ferric salt mixed solution and phosphate mixed solution dropwise to the reaction vessel at pump rates of 40ml / min and 25ml / min respectively. The synthesis reaction is carried out under the conditions of reaction temperature of 40~50℃ and stirring speed of 400rpm. Then, the mixture is kept at 90~95℃ for 60~80min to obtain precipitate. (3) The precipitate is filtered and then washed with deionized water to obtain a filter cake; after drying, ferric phosphate dihydrate powder is obtained, and then calcined at a temperature of 550℃ for 2-6 hours to obtain anhydrous ferric phosphate.

[0028] Example 3 (1) Dissolve 417.03g FeSO4·7H2O in 1.5L of deionized water and stir until completely dissolved to obtain ferrous solution. Then add it to a hydrothermal reactor, followed by 464.6g monoammonium phosphate solution. Then slowly add 84.2 mL of 30% H2O2 at a pump rate of 2.5ml / min. After the addition is complete, add 5‰ polyaspartic acid (PASP) and stir to mix evenly. Then raise the temperature to 200℃ and react at a constant temperature for 10 hours. Then cool naturally to room temperature.

[0029] (2) Weigh 1917.03g of ferrous solution and add 5mL of phosphoric acid to acidify to pH 1.5-2.5 to obtain ferric salt mixed solution A. Then weigh 464.6g of monoammonium phosphate solution and add 84.2ml of 30% hydrogen peroxide to obtain phosphate mixed solution. Use the reaction slurry in (1) as the reaction base liquid, and then add the ferric salt mixed solution and phosphate mixed solution dropwise to the reaction vessel at pump rates of 40ml / min and 25ml / min respectively. The synthesis reaction is carried out under the conditions of reaction temperature of 40~50℃ and stirring speed of 400rpm. Then, the mixture is kept at 90~95℃ for 60~80min to obtain precipitate.

[0030] (3) The precipitate is filtered and then washed with deionized water to obtain a filter cake; after drying, ferric phosphate dihydrate powder is obtained, and then calcined at a temperature of 550℃ for 2-6 hours to obtain anhydrous ferric phosphate.

[0031] Example 4 (1) Dissolve 417.03g FeSO4·7H2O in 1.5L of deionized water and stir until completely dissolved to obtain ferrous solution. Then add it to a hydrothermal reactor, followed by 464.6g monoammonium phosphate solution. Then slowly add 84.2 mL of 30% H2O2 at a pump rate of 2.5ml / min. After the addition is complete, add 5‰ polyaspartic acid (PASP) and stir to mix evenly. Then raise the temperature to 180℃ and react at a constant temperature for 6 hours. Then cool naturally to room temperature.

[0032] (2) Weigh 1917.03g of ferrous solution and add 5mL of phosphoric acid to obtain an iron salt solution. Then weigh 464.6g of monoammonium phosphate solution and add 84.2ml of 30% hydrogen peroxide to obtain a phosphate salt mixture solution. Mix the reaction slurry from (1) with the above iron salt solution, and then add the phosphate salt mixture solution dropwise to the reactor at a pump rate of 25ml / min. Then carry out the synthesis reaction at a reaction temperature of 40~50℃ and a stirring speed of 400rpm. Afterwards, keep warm at 90~95℃ for 60~80min to obtain a precipitate. (3) The precipitate is filtered and then washed with deionized water to obtain a filter cake; after drying, ferric phosphate dihydrate powder is obtained, and then calcined at a temperature of 550℃ for 2-6 hours to obtain anhydrous ferric phosphate.

[0033] Comparative Example 1 This comparative example uses the hydrothermal synthesis method in step 1 to synthesize iron phosphate. Except for the increase in the amount of feed, everything else is the same as in Example 1, that is, the product obtained after preparation by steps (1) and (3) in Example 1.

[0034] Comparative Example 2 This comparative example uses the liquid-phase precipitation method in step 2 to synthesize iron phosphate. Except for the increase in the amount of feed, everything else is the same as in Example 1, that is, the product obtained after preparation by steps (2) and (3) in Example 1.

[0035] Comparative Example 3 This comparative example is identical to Example 1 except that 5‰ polyaspartic acid (PASP) was not added in step (1).

[0036] The ferric phosphate prepared in Examples 1-4 was characterized by its microstructure. The primary particles on the surface were found to be fine millet-like and cubical in shape, and its tap density was measured to be 0.85 g / cm³. 3 about.

[0037] Weigh 500g of iron phosphate (using the iron phosphate product obtained in the above examples and comparative examples), 124g of lithium carbonate, and 18g of glucose, disperse them in pure water, and grind them until the particle size of the mixed slurry reaches 380 nm≤D50≤400 nm. Then spray dry the mixture. After sintering at 820℃ for 10h under a nitrogen protective atmosphere, a bulk material precursor is obtained. After being pulverized to a particle size D50≤2μm by an air jet mill, the precursor is dispersed in pure water containing coating agents glucose and PEG (the mass concentrations of glucose and PEG are 10% and 10%, respectively) and ground until the slurry is 400 nm≤D50≤500 nm. Then spray dry the slurry. After sintering the dried powder at 780℃ for 8h under a nitrogen atmosphere, air jet milling is performed. After pulverization, the high-pressure lithium iron phosphate powder cathode material of the corresponding example is obtained.

[0038] To verify the electrochemical performance of the lithium iron phosphate cathode material obtained in the above embodiments, the present invention prepared a slurry by mixing the obtained material in N-methylpyrrolidone at a mass ratio of LiFePO4:Super P:PVDF = 8:1:1. The slurry was coated on aluminum foil and vacuum dried at 100°C for 12 h. Then, circular electrodes were formed. The circular cathode electrodes were assembled with a separator, electrolyte, and lithium metal sheets to form a coin cell. Constant current charge-discharge cycle tests were conducted at 1C within a voltage window of 2.0~3.75V at room temperature.

[0039]

[0040] Analysis of Example 1 and Comparative Examples 1 and 2 shows that the iron phosphate prepared using a single process has a relatively simple structure. Although the iron phosphate synthesized by the hydrothermal method has a higher tap density, its rate performance is significantly lower than that of Example 1. Similarly, the iron phosphate synthesized by the single liquid-phase method has better rate performance at the lithium iron phosphate end, but its tap density is worse than that of Example 1. However, as shown in Examples 1 and 2, adding surfactants during the hydrothermal synthesis of iron phosphate helps to improve the crystallinity of the cubic phase iron phosphate and its tap density, thereby benefiting the subsequent improvement of the lithium iron phosphate end's tap density.

[0041] The above embodiments are merely illustrative examples and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations; therefore, any obvious variations or modifications derived therefrom remain within the scope of protection of this invention.

Claims

1. A method for preparing high-pressure compaction and high-capacity iron phosphate, characterized in that, Includes the following steps: Step 1: Mix the phosphate salt solution and the iron salt solution, add hydrogen peroxide dropwise, and add an appropriate amount of polyaspartic acid and / or oligo-ethoxylated fatty acid methyl esters. Then, carry out a hydrothermal reaction to generate iron phosphate slurry. Step 2: Add phosphoric acid solution to ferrous solution for acidification to obtain ferric salt mixed solution A; mix phosphate salt solution and hydrogen peroxide to obtain phosphate salt mixed solution A; Iron salt mixed solution A and phosphate salt mixed solution A were added dropwise to ferric phosphate slurry and a synthesis reaction was carried out under high-speed stirring. Then, the mixture was aged at a certain temperature and time to obtain a precipitate. The precipitate was filtered and washed to obtain a filter cake. Step 3: The filter cake is dried to obtain ferric phosphate dihydrate powder, which is then calcined to obtain anhydrous ferric phosphate.

2. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, In step 1, the iron salt solution includes at least one of ferrous sulfate, ferrous chloride, and ferrous oxalate.

3. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, In step 1, the phosphate salt includes at least one solution of ammonium hydrogen phosphate and ammonium dihydrogen phosphate; The amount of polyaspartic acid and / or oligo-ethoxylated fatty acid methyl ester added is 1-5 wt‰.

4. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, The hydrothermal reaction temperature is 160-220℃, and the hydrothermal reaction time is 3-8h.

5. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, Ferrous phosphate solution is acidified to pH 1.5-2.5 by adding phosphoric acid solution to obtain iron salt mixed solution A.

6. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, The resulting phosphate salt mixed solution A has a pH of 4.0~4.

5.

7. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, In step 2, the aging temperature is 85~95℃ and the reaction time is 1~3h.

8. The method for preparing high-pressure compaction and high-capacity iron phosphate according to claim 1, characterized in that, In step 3, the sintering temperature is 400~700℃ and the sintering time is 1~6h.

9. A type of ferric phosphate adapted for high capacity and high compaction, characterized in that, It is prepared by the method according to any one of claims 1 to 8.

10. A lithium iron phosphate, characterized in that, The iron phosphate prepared by the method described in claims 1 to 8 is used as raw material, and lithium carbonate, carbon source and additives are added and mixed, and then ground and sintered to obtain the final product.

Citation Information

Patent Citations

  • Lithium battery anode material, lithium battery anode, preparing method of lithium battery anode, and lithium battery

    CN107732201A

  • Lithium iron phosphate composite material with long cycle life, and positive electrode material, and preparation methods thereof

    CN112993227A